The Influence of Rea-Examine-Decide-Write (REDW) Strategy and Learning Motivation toward Reading Comprehension at Sriguna Junior High School of Palembang - Masagus Firdaus; Noviati Noviati (Faculty of teaching training and education, 2015)
AbstractÃ‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â This study aimed at finding out whether or not there is significant difference in reading comprehension achievements between high motivation students and low motivation students who are taught by using REDW strategy. The writer choose 30 students as the sample of the study. The sample was selected by using cluster random sampling. The data collected by using tests. The data were analyzed by using match t-test through SPSS 17 Program. The result showed that difference. This the significant difference. This obtained that the significance value was 0.030. It means that there is a significant difference in the effect of REDW strategy on reading comprehension for high or low learning motivation. Then, the significant value of learning motivation was 0.00. SinceÃ‚Â it was less than 0.05. it could be interpreted that learning motivation contributed influence on the reading comprehension. It was obtained that significance value was 0.02. There is a significant influence of REDW and learning motivation an studentsÃ¢â‚¬â„¢ reading comprehension achievement.Ã‚Â Keywords: REDW Strategy, Learning Motivation, Reading Comprehension